2018
DOI: 10.19044/esj.2018.v14n17p174
|View full text |Cite
|
Sign up to set email alerts
|

Polygyny and Resources for Empowerment and Equality in Anglo-Phone West Africa: Implications for Childbearing and Women’s Well-Being

Abstract: In West Africa, polygyny remained a common type of marriage. However, in spite of numerous studies exploring polygyny, the relationship between polygyny and access to resources for empowerment and equality is not well-ascertained in West Africa. This study addresses this gap by raising the question: to what extent does polygyny explains access to resources for empowerment and equality among married women? Data were extracted from 2013 Demographic and Health Surveys in The Gambia, Nigeria and Sierra-Leone. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…This probably reflects the economic context of polygamy, which transfers a heavy economic burden to the families of polygamous couples. This finding is supported by the study done in Afghanistan [28], West African countries and Uganda [29,30].…”
Section: Socio-economic Challengessupporting
confidence: 80%
“…This probably reflects the economic context of polygamy, which transfers a heavy economic burden to the families of polygamous couples. This finding is supported by the study done in Afghanistan [28], West African countries and Uganda [29,30].…”
Section: Socio-economic Challengessupporting
confidence: 80%
“…Given the broad scope of concerns surrounding empowerment, scholars have examined many topics across a wide range of contexts [ 33 ]. Studies have examined many topics, including educational attainment [ 37 ], political participation [ 38 ], gender-based domestic violence [ 39 ], resource control [ 40 , 41 , 42 ], entrepreneurialism [ 43 ], well-being [ 44 ], household decision-making [ 45 , 46 , 47 ], time poverty [ 48 ], and health [ 49 , 50 ]. While women’s empowerment is intrinsically important, studies in developing countries have shown that empowering women can also improve children’s health and education [ 51 ], decrease child mortality [ 52 ], improve the organizational effectiveness of businesses [ 53 ], increase agricultural productivity [ 54 ], and increase economic growth and reduce poverty [ 55 ].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Child health is poorer (Amankwaa, 1996;Amey, 2002;Arthi & Fenske, 2018;Wagner & Rieger, 2015) and child educational attainment is lower (e.g., Behaghel & Lambert, 2017). Evidence also suggests women's status is lower in polygynous families than in one-wife families (Solanke, Kupoluyi, Abe, & Bankole, 2018); polygynous wives report lower life satisfaction (Hinks & Davies, 2008) and suffer from poorer mental health; they experience more domestic violence (Ickowitz & Mohanty, 2015) and are more resigned to it (Amo-Adjei & Tuoyire, 2016;Uthman, Lawoko, & Moradi, 2009).…”
Section: Introductionmentioning
confidence: 99%